2020
DOI: 10.1007/s00216-019-02358-0
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS screening of poly- and perfluoroalkyl substances in contaminated soil by Kendrick mass analysis

Abstract: The application of contaminated paper sludge on arable land in southwest Germany caused the occurrence of a broad range of poly-and perfluoroalkyl substances (PFASs) on soil. Recently, the dead-end transformation products (TPs) perfluorooctanoic acid and perfluorooctanesulfonic acid were detected in groundwater and drinking water. The precursors and other transformation products mostly remained unknown. Therefore, HRMS screening by Kendrick mass analysis and assignment of homologous series in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…Occurrence of PFAS classes PFAS-impregnated paper samples and PFAS-contaminated soil samples were analyzed by LC-HRMS to compare patterns of homologous series of PFAS. A total of 31 individual compounds out of 8 different compound classes were identified in all samples using a previously described method [24]. The method is briefly described in the "Data evaluation" section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence of PFAS classes PFAS-impregnated paper samples and PFAS-contaminated soil samples were analyzed by LC-HRMS to compare patterns of homologous series of PFAS. A total of 31 individual compounds out of 8 different compound classes were identified in all samples using a previously described method [24]. The method is briefly described in the "Data evaluation" section.…”
Section: Resultsmentioning
confidence: 99%
“…According to Schymanski et al (2014) [36], we assigned confidence level 1a for compound identifications that were confirmed with an authentic standard; level 1b for homologues of an identified compound (1a) with systematic retention time shifts; and level 3 if only an accurate mass fit was available. No other levels were assigned (for further information on the systematic retention time shifts, see our previous publication (Bugsel & Zwiener (2020) [24])).…”
Section: Data Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most PFAS identified in this study were also reported by Houtz et al (2013) [ 49 ], Barzen-Hanson et al (2017) [ 2 ], and McDonough et al (2020) [ 29 ] for the same or similar AFFF commercial products. We qualified C 4 and C 6 perfluoroalkyl sulfonamide amino carboxylates and perfluoroalkyl sulfonamido amines that were reported by Houtz et al One pentafluorosulfide-containing eight perfluorocarbon PFAS (8-F5S-PFOS) found in AFFF was also reported by Barzen-Hanson et al We qualified four of six PFOS-substituted compounds (H-PFOS, U-PFOS, Cl-PFOS, and K-PFOS) and one of two PFDS-substituted compounds (H-PFDS) reported by McDonough et al A C 6 containing phosphonic acid and ester functional groups (8:2 monoPAP-diEes) identified in this study was detected in PFAS-contaminated soil (from paper sludge) in Germany [ 50 ]. We identified six novel PFAS that have not been otherwise detected in environmetnal samples to our knowledge: 4-FHp-CycHxA, diTF-IsoBA, Hx-diFB, Uridine-FB, and two C 4 fluoroalkyl esters (N-PFBS-MFPe, N-FBEAc).…”
Section: Discussionmentioning
confidence: 65%
“…This requires rigorous mass and data filtering, which can be streamlined using purpose-built software packages. Mass defect (MD) analysis of F-containing species is another alternative for non-targeted screening in conjunction with HRMS [26][27][28]. Mass defect analysis considers exact isotope masses and is defined as the difference between the exact mass and the nominal mass of a molecular compound.…”
Section: Introductionmentioning
confidence: 99%